Efectos subletales de dos aceites vegetales Ocotea quixos y Syzygium aromaticum en la habilidad predatoria de Hippodamia convergens en condiciones de laboratorio - Chávez Ureña, Adrian Israel (2024)
The indiscriminate use of pesticides is making an urgent call to seek for new ecofriendly alternatives to help reduce the use of the chemicals in agriculture, the biopesticides, plant-based compounds have been proposed as a tool friendlier to the environment and safer to human health. However, it ́s still unknown the full potential of these new alternative. Thus, the present investigation, using in vivo toxicological approaches, tried to evaluate the selectivity of two essential oils Ocotea quixos and Syzygium aromaticum in the predatory and locomotion behavior of the natural aphid predator, Hippodamia convergens. It was noticed that lethal concentrations (LC 95) to B. brassicae of the two essential oils listed before, didn ́t affect the predatory behavior and the locomotor activity of H. convergens. Conversely, our results showed an increasing in the number of aphids eaten in day 2 when exposed to O. quixos essential oil. To conclude, these essential oils showed a high potential to be considered in integrated pest management.